Oil, Japan - Great Britain Embassy (Japan); Great Britain Foreign Office; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 1934)
Foreign Office file containing correspondence and memoranda relating to Japanese control of Manchuria, the decisions of the Manchukuo government in relation to the oil industry in Manchuria, and the British response to Japan